Modernism keywords - Cuddy-Keane, Melba (Hoboken, New Jersey : Wiley-Blackwell, 2014)
"Modernism: Keywords presents a series of short entries explaining the diverse and often contradictory meanings of words used with frequency and urgency in "written modernism"--
Machine generated contents note: A -- Advertising -- Atom, Atomic -- Avant-Garde -- B -- Best seller -- Bigness, Smallness -- Biography, New Biography -- C -- Common Man -- Common Mind, Group Thinking -- Conventional, Conventionality -- Coterie, Bloomsbury -- D -- Democracy -- Difficulty, Obscurity -- E -- Einstein -- Empire, Imperialism -- F -- Fascism -- Form, Formalism -- G -- God, Gods -- H -- Hamlet -- Highbrow, Middlebrow, Lowbrow -- Hygiene -- I -- Impression, Impressionism -- International, Internationalism -- M -- Manifesto -- Modern, Modernism -- N -- Negro, New Negro -- P -- Personality, Impersonality -- Primitive -- Propaganda -- Q -- Queer, Gay -- R -- Race -- Readers, Reading -- Reality, Realism -- Rhythm -- S -- Sentimental, Sentimentality -- Shock, Shell Shock -- U -- Unconscious -- Universal -- W -- Woman, New Woman -- Words, Language.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: English language -- Etymology; English language -- Glossaries, vocabularies, etc; Modernism (Literature); Social structure -- Terminology; Culture -- Terminology; Sociolinguistics; Vocabulary; LITERARY CRITICISM -- American -- General; Electronic books